CCAAT/Enhancer-Binding Protein β Expressed by Bone Marrow Mesenchymal Stromal Cells Regulates Early B-Cell Lymphopoiesis. (19th February 2014) - Yoshioka, Satoshi; Miura, Yasuo; Yao, Hisayuki; Satake, Sakiko; Hayashi, Yoshihiro; Tamura, Akihiro; Hishita, Terutoshi; Ichinohe, Tatsuo; Hirai, Hideyo; Takaor-Kondo, Akifumi; Maekawa, Taira
Abstract: The transcription factor CCAAT/enhancer-binding protein β (C/EBP β ) regulates the differentiation of a variety of cell types. Here, the role of C/EBP β expressed by bone marrow mesenchymal stromal cells (BMMSCs) in B-cell lymphopoiesis was examined. The size of the precursor B-cell population in bone marrow was reduced in C/EBP β -knockout (KO) mice. When bone marrow cells from C/EBP β -KO mice were transplanted into lethally irradiated wild-type (WT) mice, which provide a normal bone marrow microenvironment, the size of the precursor B-cell population was restored to a level equivalent to that generated by WT bone marrow cells. In coculture experiments, BMMSCs from C/EBP β -KO mice did not support the differentiation of WT c-Kit + Sca-1 + Lineage − hematopoietic stem cells (KSL cells) into precursor B cells, whereas BMMSCs from WT mice did. The impaired differentiation of KSL cells correlated with the reduced production of CXCL12/stromal cell-derived factor-1 by the cocultured C/EBP β -deficient BMMSCs. The ability of C/EBP β -deficient BMMSCs to undergo osteogenic and adipogenic differentiation was also defective. The survival of leukemic precursor B cells was poorer when they were cocultured with C/EBP β -deficient BMMSCs than when they were cocultured with WT BMMSCs. These results indicate that C/EBP β expressed by BMMSCs plays a crucial role in early B-cell lymphopoiesis. Stem Cells   2014;32:730–740